Laju Kerusakan Krim Kunyit – Daun Asam (Curcuma domestica Val.-Tamarindus indica L.) pada Berbagai Konsentrasi Phenoxyethanol selama Penyimpanan - Savitri, Ni Luh Putu Devi; Triani, I Gusti Ayu Lani; Wrasiati, Luh Putu (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 10 No 1 (2022): MaretDO - 10.24843/JRMA.2022.v10.i01.p03, 2022)
This study aims to determine the relationship between the concentration of phenoxyethanol on the rate of deterioration of turmeric-tamarind cream and to determine the appropriate concentration of phenoxyethanol so as to produce turmeric-tamarind cream with a longer shelf life and meet SNI requirements. This study uses a linear regression analysis, with phenoxyethanol concentration treatment consisting of 6 levels, namely 0%; 0 . 2%; 0 . 4%; 0 . 6%;0 . 8% and 1%. The treatment was repeated 3 times so that there were 18 experimental units. The objective data obtained were analyzed using linear regression to determine the rate of deterioration of turmeric-tamarind cream during storage. The variables were observed in this study is homogeneity, ph, the specific gravity, viscosity, total phenolic, total plate count (ALT) and molds/yeasts (AKK). The results showed that the best concentration of phenoxyethanol preservative concentration was P6 (1%) treatment with a ph value of 5 . 46, specific gravity 0 . 99038 g/cm 3 , viscosity 10000 cps, total phenol 33 . 60036 mg GAE/g, ALT 0 colony/g and AKK 0 colony/g . Keywords : Turmeric, Tamarind leaves, Phenoxyethanol, Shelf life